Long‐term biochar application governs the molecular compositions and decomposition of organic matter in paddy soil - Jiali Sun (Wiley, 2021)
Abstract Biochar addition can enhance soil quality and sequester carbon. However, changes in soil organic matter (SOM) molecular compositions in response to long‐term biochar addition have rarely been studied. Therefore, we quantified soil organic carbon fractions, carbon‐cycling enzyme activities, and a range of organic compounds and lignin‐derived phenols in the rhizosphere and bulk soils in different rice growth stages in the 8‐year field trial with biochar application rates of 0 (BC‐0), 4.5 (BC‐L), and 13.5 t ha−1 year−1 (BC‐H). We found that higher amounts of biochar addition (BC‐H) increased labile organic carbon (LOC), dissolved organic carbon (DOC) and particulate organic carbon (POC), and promoted activities of α‐1,4‐glucosidase, β‐D‐cellobiohydrolase and β‐1,4‐xylosidase; in contrast, BC‐L treatment reduced activities of these enzymes. The concentrations of dichloromethane/methanol‐extractable plant‐ and microbial‐derived organic compounds in the rhizosphere and bulk soils at tillering decreased significantly in the treatment with low amount of biochar addition. BC‐L also significantly altered the concentrations of extracted compounds in the rhizosphere soil at tillering and harvest. Concentration of lignin in the bulk soil was significantly reduced in BC‐L at tillering (by 19%) and harvest (by 28%). The concentrations of extracted compounds (e.g., n‐alkanols, n‐alkanoic acids, steroids, and carbohydrates) and lignin were generally significantly higher in the bulk than the rhizosphere soil at tillering and harvest. Long‐term biochar application (BC‐H) promoted lignin decomposition in the bulk soil (at tillering) and the rhizosphere soil (at harvest). Hence, biochar decreased stability of lignin in paddy soil. Our study provided evidence that long‐term biochar application changed the molecular composition and dynamics of degradation of SOM. These results deepen our understanding of the mechanisms governing SOM stability in agricultural ecosystems.